2019
DOI: 10.1038/s41594-019-0324-9
|View full text |Cite
|
Sign up to set email alerts
|

UPR proteins IRE1 and PERK switch BiP from chaperone to ER stress sensor

Abstract: BiP is a major ER chaperone and suggested to act as primary sensor in the activation of the unfolded protein response (UPR). How BiP operates as a molecular chaperone and as an ER stress sensor is unknown. Here, by reconstituting components of human UPR, ER stress and BiP chaperone systems, we discover that the interaction of BiP with the luminal domains (LD) of UPR proteins, IRE1 and PERK, switch BiP from its chaperone cycle into an ER stress sensor cycle by preventing the binding of its cochaperones, with lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
163
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 249 publications
(188 citation statements)
references
References 34 publications
2
163
0
1
Order By: Relevance
“…PERK (encoded by the Eif2ak3 gene) is a type I ER transmembrane protein, its protein kinase activity at the carboxyl terminus of its cytoplasmic segment is the main functional region and can phosphorylate eIF2α at protein serine 51 and also autophosphorylate 4,43 . The role of PERK in skeletal development and remodeling has been widely concerned.…”
Section: Discussionmentioning
confidence: 99%
“…PERK (encoded by the Eif2ak3 gene) is a type I ER transmembrane protein, its protein kinase activity at the carboxyl terminus of its cytoplasmic segment is the main functional region and can phosphorylate eIF2α at protein serine 51 and also autophosphorylate 4,43 . The role of PERK in skeletal development and remodeling has been widely concerned.…”
Section: Discussionmentioning
confidence: 99%
“…This is further complimented by pull-down interaction analysis and chemical cross-linking that similarly observe a direct interaction with BiP NBD [ 50 ]. A recent structure-guided mutational study identified a mutation within the NBD that severely reduced the affinity for binding to IRE1 [ 51 ]. Furthermore, in another mutational-based study that was conducted in yeast cells, it was suggested that the interaction with IRE1 was again mediated via BiP NBD [ 52 ].…”
Section: Hsp70 Specialized Interactions At the Membranementioning
confidence: 99%
“…In non-stressed cells, the highly abundant major ER chaperone and ER stress sensor binding-immunoglobulin protein BiP (also called 78 kDa glucoseregulated protein, GPR78; heat shock protein family A member 5, HSPA5) binds to PERK and IRE1α, which keeps these two proteins in an inactive monomeric state (Bertolotti et al, 2000;Pobre et al, 2019). Upon increased binding of BiP to misfolded ER clients, BiP is released from both PERK and IRE1α, resulting in an (indirect) activation of the two kinases by oligomerization and trans(auto)phosphorylation (Carrara et al, 2015;Cui et al, 2011;Kopp et al, 2019). Active PERK phosphorylates the eukaryotic translation initiation factor 2 (eIF2) subunit α to shut down translation and also activates ATF4, the master transcription factor orchestrating ER stressinduced genes (Han et al, 2013;Urra & Hetz, 2017).…”
Section: Introductionmentioning
confidence: 99%